Design and development of friction less automotive transmission: performance analysis of input and output torque / Abdul Khalik Muhammad Fakhruddin - Muhammad Fakhruddin, Abdul Khalik (2009)
Infinitely Variable Transmission (IVT) is currently being the matter of interest in automotive industry due to its capability to improve fuel economy and performance of the vehicle. This project will introduce a new design of frictionless transmission with infinitely variable speed ratio. This transmission is design to eliminate friction process by clutch disk and allowing engine to operate at its most optimum condition. High torque generated by rotating mass is the main concept in developing this transmission. This work will describe the operating principle of the friction less transmission referring to its design drawing. Several simple physic approaches are used to initially analyze the torque performance theoretically. The model of the transmission has been design and developed. Variable speed motor will be acted as input torque. Analysis on output torque generated by the transmission is done by using Spring Scale to measure force exerted at the output shaft. From this, the performance of the friction less transmission can be analyzed.